Features of the treatment of elderly patients with coronary heart disease at the stages of 1990, 2010 and 2017 examinations. - I. S. Shapovalenko (Medičnì Perspektivi)
The purpose of the work is to determine the characteristics of prescription, adherence to treatment and the effect of certain classes of drugs used for the treatment of cardiovascular diseases on the life expectancy of elderly patients with ischemic heart disease (IHD). 517 case histories of patients aged 60-87 (–91) years old, born in 1925-1957 with IHD were analyzed. All the examined were first hospitalized in the hospital and later were observed with the main diagnosis of coronary artery disease: stable exertional angina I-IV FC. Further observation of the patients lasted from 3 to 25 years (average observation period 10 years), until reaching the endpoint or until the last observation in 2017. The patient’s death was chosen as the endpoint, on the basis of which the life expectancy index (determined by the year / age of death) was studied. It has been shown, that therapeutic regimens for the elderly patients with coronary artery disease meet current standards for the treatment of coronary artery disease at the stages of 1990, 2010 and 2017. Patients' adherence to therapy was 82.4%. According to the data obtained, the association of taking certain classes of drugs with the life expectancy of patients was: ACE inhibitors increase life expectancy by 7 years, acetylsalicylic acid (ASA) - by 4 years, statins and β-blockers - by 2 years. The most effective combinations for treating people with IHD that affect life expectancy are: combinations of ASC, statins and ACE inhibitors - survival up to 80.14±3.16 years, ASA, statins and Ca-channel blockers - survival up to 80±1.71 years, ASC, statins and β-blockers - survival to 79.3±4.24 years, ASA and ACE inhibitors - survival to 79.59±3.83 years.